PROSTITUCIÓN. ANÁLISIS JURÍDICO SOBRE SU REGULACIÓN Y LEGITIMIDAD EN COLOMBIA (2022)
Around prostitution, in Colombia a debate has been developed focused on the concretization of the position of the legal system about its legitimacy and regulation in relation to the dichotomy posed by opposing positions such as regulation, implying constitutional and legal recognition in matters of labor rights; abolitionism, based on the consideration of prostitution to be contrary to the human dignity, and prohibitionism. This topic takes on special importance when observing the social impact generated by the exercise of prostitution, both in those who participate directly in its activity, and in society in general. The analysis will be carried out based on the examination of the legal, doctrinal and jurisprudential framework; Scenarios through which the recognition and protection of prostitution through the law has been sought. Finally, based on the investigative work, it is recognized that the Colombian legal system is far from having a defined position on the subject. However, the existence of a guaranteeing vision of the rights of those who exercise prostitution is highlighted, as they are recognized as subjects in a special situation of vulnerability, the above, based on human dignity and freedom.